ChemInform Abstract: Recoverable Silica‐Gel Supported Binam‐Prolinamides as Organocatalysts for the Enantioselective Solvent‐Free Intra‐ and Intermolecular Aldol Reaction. Issue 24 (23rd May 2013) - Banon‐Caballero, Abraham; Guillena, Gabriela; Najera, Carmen; Faggi, Enrico; Sebastian, Rosa Maria; Vallribera, Adelina
Abstract Two novel heterogeneous BINAM‐prolinamides are prepared and evaluated as chiral catalysts for the intermolecular aldol reaction of different substrates.